Senyawa Volatil Daging Celeng (Sus scrofa vittatus) dengan Berbagai Pengolahan Menggunakan Metode SPME-GC/MS - Amalia, Lia; Novidahlia, Noli; Kusumaningrum, Intan; Mulya, Sahnur; Mardiah; Jumiono, Aji; Eliska, Arshyla; Ramadhan, Muhamad Fauzi; Lidiyani, Nurfitri (JURNAL AGROINDUSTRI HALAL, 2025)
Food adulteration involving the mixing of non-halal meat into halal products is a sensitive issue in Indonesia. Wild boar meat (Sus scrofa vittatus) is often found to be used in such practices, making it essential to identify its volatile compound profile. This study aims to identify volatile compounds in wild boar meat processed through boiling, frying, and roasting, using Solid-Phase Microextraction (SPME) combined with Gas Chromatography-Mass Spectrometry (GC-MS). The research was conducted qualitatively with three treatments and five replications for each cooking method. The analysis showed that boiled wild boar meat contained 156 volatile compounds, fried meat 142 compounds, and roasted meat 163 compounds, with total intensities of 779, 691, and 819, respectively. Principal Component Analysis (PCA) yielded an R²X value of 0.842 and a cumulative Q² of 0.747, indicating clear separation between samples. The main contributing volatile compounds were 2-Octenal (E)-, Longifolene, and Cyclopropyl carbinol.